CAPITAL STRUCTURE MANAGEMENT PRACTICES AND MARKET VALUE OF NIGERIA LISTED MANUFACTURING FIRMS - Oluwatimileyin Esther ADENLE; Aderemi Olalere ADEBAYO; Peter Sunday DARAMOLA (Malete Journal of Accounting and Finance)
A well-managed capital structure can lower perceived risk and boost market value through increased investor confidence whereas an ineffective capital structure will result into higher risk and lower market value. This research therefore examined the effect of capital structure management practices on the market value of quoted Nigerian manufacturing firms from year 2013 to 2022. Out of the total population of 44 companies, 30 were specifically selected from the consumer products, agricultural, industrial goods, and conglomerate industries using purposive sampling technique. For data analysis, the study used descriptive statistics, panel regression, and correlation analysis. The findings showed that market share prices were significantly impacted by the debt-equity ratio (DER) and financial autonomy rate (FAR), with p-vals. (0.043, 0.021 < 0.05) and t-stat. (-2.02, -2.32), respectively. Additionally, FAR, operating cash ratio (OPR), and DER had a favourable and noteworthy impact on Tobin’s Q, supported by t-statistics and p-values (-2.14, 2.35, 2.42) and (0.032, 0.019, 0.016 < 0.05) respectively. The study comes to the conclusion that the market value of the chosen listed Nigerian manufacturing companies is significantly impacted by capital structure management techniques. It suggests that in order to take advantage of the tax shield, manufacturing firms management should strive for the ideal balance between debt and equity and should utilize cash flow for investment in growth opportunities.